Retailing management - Levy, Michael; Weitz, Barton A. (Harvard University Press, 2009)
Retailing Management by Levy and Weitz continues to be the market-leading text for the retailing course through its readability, organization, and emphasis on how students can come to grips with real retailing issues while being able to solve problems. The text's logical decision-making focus allows students to discover the process of strategic decisions first before moving on to implementation. Students indicate that this text is "good read" because of the numerous examples of retailers, their practices, the interesting retail facts in the margins, and eye catching design and layout.